African swine fever knowledge, attitudes and practices of pig farmers of Saint Kitts, Nevis, Saint Eustatius, Saint Lucia and Saba; West Indies - Hervé-Claude, Luis Pablo; Gallagher, Christa; Navarrete-Talloni, Maria Jose; Boden, Lisa; Villanueva-Cabezas, Juan Pablo (Frontiers in Veterinary Science, 2025)
IntroductionAfrican Swine Fever (ASF) is an important transboundary animal disease that was re-introduced to the Americas in 2021 and is at risk of spreading through the Caribbean region. There is an active outbreak of ASF in the Dominican Republic and Haiti, and risk of onward transmission which could affect other islands, including the West Indies. If further spread of ASF occurs, pig farmers are likely to play a key role in prevention and response to an incursion of the disease. However, there is limited data about the demographics, knowledge, attitudes and practices (KAP) of pig producers in the West Indies.MethodsThis study aims to describe swine production and trade within five island territories and to collect KAP data using a survey to improve pig husbandry practices and inform African Swine Fever disease control and preparedness.ResultsPig production in this region appears to be dominated by backyard, smallholder farms with active intra-island trade and important deficiencies in biosecurity. Few farmers have any knowledge on ASF, as only 29.6% (21/71) indicated to have some knowledge about ASF. Commercial feed use is widespread (95.7% of farms, 68/71), as is the feeding of household scraps (57.8%, 41/71). International legal live pig trading is limited in its frequency and volume.DiscussionThe heterogeneous political, cultural and geographical nature of the West Indies means that it is important to consider each island territory individually to appreciate and consider contextual aspects of pig production for improved preparedness. Farmers in this study proved to have little knowledge on ASF, practice some high-risk behaviors (swill & scrap feeding) and lack adequate biosecurity practices to keep the region safe from ASF.